Estimating the impact of the recent economic crisis on work time in turkey - Emel Memiş; S. A. Kaya Bahçe (Levy Economics Institute of Bard College, 2011)
This paper provides estimates of the impact of the recent economic crisis on paid and unpaid work time in Turkey. The data used in this study come from the first and only time-use survey available at the national level. Infrequency of collection of time-use data in Turkey does not allow us to make a direct comparison of pre-versus postcrisis time-use patterns. We introduce a tractable way for estimating these possible effects by measuring the impact of an increase in unemployment risk on time-use patterns of women and men living in couple households. The method developed here can be applied to other developing-country cases where there is a lack of longitudinal data availability. Our findings support the argument that economic crises reinforce the preexisting gender inequalities in work time.
Keywords: B54; J16; J22; 330; economic crisis; gender inequality; time use; unemployment risk; unpaid work; Turkey